Ultrasonic Assisted Equal Channel Angular ‎Extrusion Process ‎‎(UAECAE)‎ - Hamed Razavi; Yaghoub Tadi Beni; Mohammad Baharvand (International Journal of Advanced Design and Manufacturing Technology, 2017)
Equal channel angular extrusion (ECAE) is one of the most powerful processes for manufacturing microstructure and nanostructure ‎materials. This process is a kind of severe plastic deformation technique, which requires large extrusion force. In this study, the numerical and experimental investigation of extrusion ‎force in ultrasonic assisted equal channel angular extrusion process (UAECAE) is carried out. ABAQUS Software is used for 2D ‎finite element analysis of the process considering superimposed ultrasonic vibrations to the round billet work material. Experimentally, the conventional and ultrasonic assisted ECAE are performed with copper material to validate simulation results. The reduction in extrusion force is observed due to ultrasonic vibrations. In order to achieve more ‎average force reduction, it is recommended that the ‎extrusion speed decreases and (or) vibrations amplitude ‎increases. Stress and strain distributions are numerically investigated in various vibrational conditions and die angles. The best die angle to obtain optimum force ‎reduction is 120º. In other die angles, vibrations ‎amplitudes of 15‎ μm‎ and higher ‎is necessary. Ultrasonic vibrations lead to oscillatory stresses with reduced ‎average value, but do not influence the amount of plastic strain ‎distribution. Achieving the beneficial products in ‎ECAE requires heavy special equipment, whereas using UAECAE will lead to more accessible equipment. ‎Finally, some optimal process parameters such as die angle, vibrations amplitude, for the proper application of these vibrations are ‎proposed.